Postharvest melatonin treatment inhibited longan (Dimocarpuslongan Lour.) pericarp browning by increasing ROS scavenging ability and protecting cytomembrane integrity. Issue 9 (5th July 2021) - Luo, Tao; Yin, Feilong; Liao, Lingyan; Liu, Yunfen; Guan, Boyang; Wang, Min; Lai, Tingting; Wu, Zhenxian; Shuai, Liang
Abstract: Postharvest melatonin treatments have been reported to improve the quality and storability, especially to inhibit browning in many fruits, but the effect had not been systematically investigated on longan fruit. In this study, the effect of 0.4 mM melatonin (MLT) dipping on the quality and pericarp browning of longan fruits stored at low temperature was investigated. The MLT treatment did not influence the TSS content of longan fruits but lead to increased lightness and h° value while decreased a* value of pericarp. More importantly, the treatment significantly delayed the increase in electrolyte leakage and malonaldehyde accumulation, inhibited the activities of polyphenol oxidase and peroxidase, and thus retarded pericarp browning. In addition, the treatment significantly inhibited the production of O2 − and H2 O2 while promoted the accumulation of glutathione, flavonoids, and phenolics at earlier storage stages in longan pericarp. Interestingly, the activities of ascorbate peroxidase (APX) and superoxide dismutase (SOD) were significantly upregulated but activities of catalase were downregulated in the MLT‐treated longan pericarp. MLT treatment effectively enhanced APX and SOD activities, increased flavonoid, phenolics, and glutathione content, protected cytomembrane integrity, inhibited the production of O2 − and H2 O2 and browning‐related enzymes, and thus delayed the longan pericarp browning. Abstract : Our results showed that 0.4 mM melatonin (MLT) dipping significantly increased the ROS scavenging ability by enhancing the activities of SOD and APX as well as increasing the content of GSH, phenolics, and flavonoids (especially at the earlier storage stages). This might result in the decreased level of O2 − and H2 O2 and lower MDA (membrane lipid oxidation products) content, and thus, the treatment protected the cytomembrane integrity and prevented the pericarp from enzymatic browning by PPO and POD. In conclusion, postharvest melatonin treatment inhibited longan pericarp browning by increasing ROS scavenging ability and protecting cytomembrane integrity.